RTA and LANA Competitively Regulate let-7a/RBPJ Signal to Control KSHV Replication - Di, Chunhong; Zheng, Guoxia; Zhang, Yunheng; Tong, Enyu; Ren, Yanli; Hong, Yu; Song, Yang; Chen, Rong; Tan, Xiaohua; Yang, Lei (Frontiers in Microbiology, 2022)
The recombination signal binding protein for immunoglobulin kappa J region (RBPJ) has a dual effect on Kaposi's sarcoma-associated herpesvirus (KSHV) replication. RBPJ interaction with replication and transcription activator (RTA) is essential for lytic replication, while the interaction with latency-associated nuclear antigen (LANA) facilitates latent infection. Furthermore, our previous study found that LANA decreased RBPJ through upregulating miRNA let-7a. However, it is unclear whether RTA regulates the expression of RBPJ. Here, we show RTA increases RBPJ by decreasing let-7a. During KSHV replication, the RBPJ expression level was positively correlated with the RTA expression level and negatively correlated with the LANA expression level. The let-7a expression level was inverse to RBPJ. Knockdown of RBPJ inhibited the self-activation of RTA promoter and LANA promoter and weakened LANA's inhibition of RTA promoter. Collectively, these findings indicate that RTA and LANA compete for let-7a/RBPJ signal to control the KSHV replication. Regulating the RBPJ expression level by RTA and LANA plays an important role during KSHV replication.